DRhigh+CD45RA−-Tregs potentially affect the suppressive activity of the total Treg pool in renal transplant patients - Schaier, Matthias; Seißler, Nicole; Meuer, Stefan; Hug, Friederike; Zeier, Martin; Steinborn-Kröhl, Andrea (PLOS ONE, 2012)
Recent studies show that regulatory T cells (Tregs) play an essential role in tolerance induction after organ transplantation. In order to examine whether there are differences in the composition of the total CD4+CD127low+/−FoxP3+- Treg cell pool between stable transplant patients and patients with biopsy proven rejection (BPR), we compared the percentages and the functional activity of the different Treg cell subsets (DRhigh+CD45RA−-Tregs, DRlow+CD45RA−-Tregs, DR−CD45RA−-Tregs, DR−CD45RA+-Tregs). All parameters were determined during the three different periods of time after transplantation (0-30 days, 31-1,000 days, >1,000 days). Among 156 transplant patients, 37 patients suffered from BPR. The most prominent differences between rejecting and non-rejecting patients were observed regarding the DRhigh+CD45RA−-Treg cell subset. Our data demonstrate that the suppressive activity of the total Treg pool strongly depends on the presence of these Treg cells. Their percentage within the total Treg pool strongly decreased after transplantation and remained relatively low during the first year after transplantation in all patients. Subsequently, the proportion of this Treg subset increased again in patients who accepted the transplant and reached a value of healthy non-transplanted subjects. By contrast, in patients with acute kidney rejection, the DRhigh+CD45RA−-Treg subset disappeared excessively, causing a reduction in the suppressive activity of the total Treg pool. Therefore, both the monitoring of its percentage within the total Treg pool and the monitoring of the HLA-DR MFI of the DR+CD45RA−-Treg subset may be useful tools for the prediction of graft rejection.